Writing matters: in conversation with Dr. Mohammad A. Quayum - Dutta-Asane, Sucharita; Quayum, Mohammad Abdul; ., Shikhandin (Kitaab Publishing, 2018)
Interview session between Sikhandin with Dr.Mohammad A. Quayum discussing on various aspects of South and Southeast Asian literature.